Effect of Dahuang Danpi Decoction on Lactobacillus bulgaricus growth and metabolism: In vitro study. Issue 5 (February 2019) - Li, Chaoqun; Zhang, Jiayu; Xu, Hua; Chen, Yabin; Gao, Shuoshuo; Guo, Shu-ning; Huang, Bang; Gao, Ruyi; Long, Zhicheng; Jiang, Meirong
Abstract : Abstract: Gut flora plays an essential role in disease and health. A traditional Chinese herb formula, Dahuang Danpi Decoction (DDD) can alleviate several gastrointestinal diseases. In the present study, we assessed the effect of DDD on the growth and metabolism of Lactobacillus bulgaricus . L bulgaricus was cultured in MRS with 40 mg/ml (high), 10 mg/ml (medium), and 2.5 mg/ml (low) of DDD, Ceftriaxone and blank (control). The growth of L bulgaricus was measured by optical density. The levels of L-lactic acid and D-lactic acid were also measured. Compared to the control group, the concentrations of L bulgaricus in the medium and the high concentrations DDD groups were significantly higher ( P <  .001 for all), while the concentrations of L bulgaricus in the ceftriaxone groups were significantly lower. In the 3 DDD groups, the L- lactic acid levels were significantly higher than those in the control group and the ceftriaxone groups ( P <  .001 for all), and the L-lactic acid level was the highest in the high DDD group. Similarly, the D-lactic acid level in the high concentration DDD group was significantly higher than those in the medium and low concentration DDD groups, the control group and the ceftriaxone groups. Both the L-lactic acid and D-lactic acid levels were lower than those in the control group and the DDD groups. DDD could dose-dependently promote the growth of L bulgaricus and enhance the secretion of L-lactic acid and D-lactic acid, which suggests DDD may be able to interact with the probiotics, improve the gut microbiota, and serve in the prevention and treatment of dysbiosis.